Fisioterapia Nefrológica: Mejora De La Calidad De Vida Mediante Un Programa De Acondicionamiento Físico En Pacientes Con Enfermedad Renal Crónica En Una Unidad De Hemodiálisis En Mexico - Ovando, Itzel Yeyetzin González; Malagón, Genaro Vega (European Scientific Journal, ESJ, 2017)
Objective: To analyze the improvement of the quality of life in the physical sphere through an effective physiotherapy program of physical conditioning in patients with Chronic Renal Disease in the Hemodialysis Unit in México. Methodology: Prospective longitudinal comparative study, pre and post treatment, in which the efficacy of a physiotherapeutic intervention and treatment and its impact on the quality of life during 20 weeks in a group of 25 patients with chronic renal disease undergoing hemodialysis were quantified. To evaluate the efficacy of the treatment, the study was divided into 5 stages and the KDQOL-SFTM questionnaire. Results: Results: In the physical sphere measured by the applied KDQOLSF ™ instrument, the best results have been obtained, since statistically significant differences (p <0.05) were found between the variables of the decrease in difficulty in bending and bending M 2.28 DE (0.842) versus M 2.64 DE (0.700) P 0.047, loads and transfers M 2.08 D.E (0.953) versus M 2.48 D.E (0.714) P 0.015, and decrease in difficulty in bathing and dressing (MV) M 2.56 D.E. (0.711) versus M 2.88 D.E (0.331) P 0.029, variables analyzed in the pre and post physiotherapeutic intervention, respectively. Conclusion: All patients showed a significant improvement in strengthresistance thanks to the physical-fitness program intradiálisis, increased the functional capacity and improved the physical sphere component of the quality of life of patients with Chronic Renal Disease.